Malnutrition Challenge Therapeutic Strategy - Syed Hafeez ul Hassan (Aziz Fatimah Medical and Dental College, 2019)
SUMMARY Malnutrition is a broad term which describes nutritional related diseases caused by over and under nutrition, found in the hospitals or in famines. Therefore malnutrition can be categorized as over nutrition and obesity resulting into metabolic syndrome characterized by hyperglycemia, hypertension, dyslipidemia, hyperuricemia and decreased vitamin D in some cases. Whereas under nutrition with inflammation can be as a result of chronic illness, acute illness/injury or simply decreased dietary intake when there is no inflammation. The initial assessment can be done by simple clinical measures such as recording weight and BMI and serum albumin estimation. The adjusted nutrition plan during sickness involves assessment of calories requirement under the circumstances and then to use appropriate nutrition or premade nutrition formulas to meet the new requirements during disease or after surgery. The therapeutic strategy which also includes nutrition assessment and treatment may result in decrease in complications hence decreased hospital stay and cost of treatment having better hospital outcomes.